Persepsi Nasabah Terhadap Bank Syariah di Indonesia - Mustakim Muchlis (ITB AAS INDONESIA Surakarta, 2021)
This research aims to examine customer interest in Islamic banking as an attempt to obtain information that can be used by related parties to make improvements in the dominance of Islamic banking in Indonesia. This study is a qualitative study using an interpretative paradigm. The results of the survey showed that customer perception of Islamic banks towards Islamic banks was good and continues to support performance by faithfully using the products issued. Meanwhile, non-Muslim banking customers said that Islamic banking support facilities are currently lacking, so they have no interest in using Islamic banking products.